The Role of SNPs in the Pathogenesis of Idiopathic Central Precocious Puberty in Girls - Konstantina Toutoudaki; George Paltoglou; Dimitrios T. Papadimitriou; Anna Eleftheriades; Ermioni Tsarna; Panagiotis Christopoulos (MDPI AG, 2023)
The initiation of puberty is a crucial timepoint of development, with its disruptions being associated with multiple physical and psychological complications. Idiopathic Central Precocious Puberty (iCPP) has been correlated with Single-Nucleotide Polymorphisms (SNPs) of certain genes that are implicated in various steps of the process of pubertal onset. The aim of this review was to gather current knowledge on SNPs of genes associated with iCPP. We searched articles published on the PubMed, EMBASE and Google Scholar platforms and gathered current literature. KISS1, KISS1R, PLCB1, PRKCA, ITPR1, MKRN3, HPG axis genes, NPVF/NPFFR1, DLK1, KCNK9Q, LIN28B, PROK2R, IGF-1, IGF2, IGF-1R, IGF-2R, IGFBP-3, insulin, IRS-1, LEP/LEPR, PPARγ2, TAC3, TACR3, Estrogen receptors, CYP3A4 and CYP19A1 were studied for implication in the development of precocious puberty. SNPs discovered in genes KISS1, KISS1R, PLCB1, MKRN3, NPVF, LIN28B, PROK2R, IRS-1 TAC3, and CYP3A4 were significantly correlated with CPP, triggering or protecting from CPP. Haplotype (TTTA)13 in CYP19A1 was a significant contributor to CPP. Further investigation of the mechanisms implicated in the pathogenesis of CPP is required to broaden the understanding of these genes' roles in CPP and possibly initiate targeted therapies.